Development and root morphology of passion fruit in different substrates - Valle, Karminne Dias do; Pereira, Laísse Danielle; Barbosa, Moab Acácio; Chaves, Vanessa Brenda Souza; Souza, Pedro Henrique Magalhães de; Reis, Edésio Fialho dos; Hurtado-Salazar, Alejandro; Silva, Danielle Fabíola Pereira da (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
Among the factors that contribute to better initial development of plants, it is the substrate used. Therefore, this study aimed to evaluate the effect of substrate in initial formation and morphology of the roots of two species of passion fruits. The analyses were done in the nursery of the Federal University of Goiás (UFG), Regional Jataí, Brazil, with a light interception of 60%. The material used were seeds of yellow passion fruit (Passiflora edulis f. flavicarpa) and the cultivar FB 200 (Flora Brasil), harvested in the UFG experimental field. They were sown in three types of substrates: Soil I (mixture of soil, chicken manure and sand in a ratio of 2:1:1 by volume), soil II (steep bank), and Bioplant®, using for plants perforated bags with a capacity of 1.5 L. The experimental design was a completely randomized design with six treatments, eight replications and four plants per plot. After 30 days of sowing, fresh matter of root, root dry matter and morphology were evaluated. The substrate affected the initial development of yellow passion fruit, obtaining the best results with Bioplant®, showing as promising for the development of all the evaluated characteristics.